2017
DOI: 10.1007/s41114-017-0007-y
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical boson stars

Abstract: The idea of stable, localized bundles of energy has strong appeal as a model for particles. In the 1950s, John Wheeler envisioned such bundles as smooth configurations of electromagnetic energy that he called geons, but none were found. Instead, particle-like solutions were found in the late 1960s with the addition of a scalar field, and these were given the name boson stars. Since then, boson stars find use in a wide variety of models as sources of dark matter, as black hole mimickers, in simple models of bin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
142
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(145 citation statements)
references
References 379 publications
(671 reference statements)
3
142
0
Order By: Relevance
“…Remarkably, because the scalar field does not share the isometries of the spacetime, it is possible to evade the no-hair theorems when the angular velocity of a Kerr black hole matches the angular parameter m/ω s of a marginal scalar cloud, giving rise to a hairy black hole as reported in [28]. An updated review on boson stars can be found in [29].…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, because the scalar field does not share the isometries of the spacetime, it is possible to evade the no-hair theorems when the angular velocity of a Kerr black hole matches the angular parameter m/ω s of a marginal scalar cloud, giving rise to a hairy black hole as reported in [28]. An updated review on boson stars can be found in [29].…”
Section: Introductionmentioning
confidence: 99%
“…We are after a practically useful generalization of the WGC and are therefore not satisfied with the possible and fairly obvious statement that all bound states not protected by gauge invariance must decay. 4 For a review on boson stars (updated in 2017) see [29]. A selection of recent work can be found in [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] the heaviest elementary state has mass m , no bound state with radius below the scale 1/m set by the Compton wavelength exists.…”
Section: Introductionmentioning
confidence: 99%
“…α-particles are not reactive for certain temperature range, even if sufficient energy for fusion reactions as much as 10 MeV per nucleon is provided. Meanwhile the soliton star is a long-standing concept whose existence is proposed in association with the relativistic gravitational force field [27] (for a textbook of bosonic stars, soliton stars and the related topics, see [28]). The energy of such proposed soliton stars (comparable to the energy of black holes) is much higher than the present low-temperature solitonic core.…”
Section: Calculations and Discussionmentioning
confidence: 99%